2021
DOI: 10.3390/su13042115
|View full text |Cite
|
Sign up to set email alerts
|

Green Strategy Effect on Financial and Environmental Performance: A Mediation Analysis of Product Quality

Abstract: The dilemma of firms in developing economies was the crux of this study. In probing whether the adoption of organization-wide green strategy would enhance the product quality and the firm’s financial lifeline, while also improving the environment, we developed a mediation model. The specific objectives were to ascertain the direct effect of green strategy on both environmental and financial performance and its total effect on both environmental and financial performance through product quality. With data colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 65 publications
6
22
0
5
Order By: Relevance
“…This supports the results from the previous studies such as Ref. [16,20,52,53]. Batik MSMEs need to implement GS which must be integrated with the program, policy, and budget they owned.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This supports the results from the previous studies such as Ref. [16,20,52,53]. Batik MSMEs need to implement GS which must be integrated with the program, policy, and budget they owned.…”
Section: Discussionsupporting
confidence: 87%
“…Tjahjadi et al [53] added that choosing and implementing green innovation strategy can have a significant impact on business performance. The results from the study conducted by Olayeni et al [16] also showed that GS can increase environmental and financial performance.…”
Section: Green Strategy (Gs) and Ce Implementationmentioning
confidence: 88%
See 1 more Smart Citation
“…It was possible to support the decision regarding the prediction of the quality of biofuels being product-friendly for the environment. In turn, in [20], the prediction of organization finance results based on product quality and organization ecological strategy was supported. It was shown that the acceptance of a green strategy maintains financial profitability by simultaneously concentrating on product quality.…”
Section: Introductionmentioning
confidence: 94%
“…It has been shown that the product quality level can be predicted [14][15][16][17][18]. In addition, the impact of products on the natural environment can be predicted [19][20][21][22]. However, a model that allows for the prediction of pro-quality decisions while simultaneously considering qualitative and environmental aspects is lacking.…”
Section: Introductionmentioning
confidence: 99%